Comparing Biocompatibility and Efficacy of Hydroxyapatite Nanocomposites at Nano-level for its Biomedical Application: A Systematic Review - Durgha , Sakthi R.S.; Sindhu , R.; Prabu , D.; Rajmohan , M.; Bharathwaj , V.V.; Dinesh , Dhamodhar M.; Sathiyapriya (International Journal of Scientific Research in Biological Sciences, 2023)
Aim: To evaluate the biocompatibility and efficacy of various nano-functionalised hydroxyapatite nanocomposites by reviewing several in-vitro studies conducted to test its potential effects on human cell lines and animal cell lines. Methods: A survey of relevant scientific data was done utilizing Pubmed, Ovid Medline, Cochrane Library, Wiley Online Library, Science Direct, Scientific Reports, Grey literature, CINAHL, IOPscience, National library of medicine, Advanced Ceramic Progress, Hindawi, MDPI, JPSR, ACS, Springer, and by using MeSH "Hydroxyapatite nanocomposites and its biocompatibility and efficacy". As stated in Prisma guidelines, in search engines, these words were improved. Results: All four reviewed articles showed positive effects of Hydroxyapatite nanocomposites on their biocompatibility. HA/Au and HA/Pd showed negative results concerning osteoinduction and osteogenesis properties, whereas HA/MAG showed positive results. HA-natural polymers composite showed no cytotoxicity. The bioactive HA/Gr composite coating manifested no cytotoxicity and no antibacterial properties. HA/PCL composite improved cell adhesion and cell proliferation. Statistically, significant improvement in the biocompatibility and efficacy using nano-functionalised hydroxyapatite composites when compared to non-functionalised hydroxyapatite nanocomposites with p< 0.01 Conclusion: From the available scientific sources, Hydroxyapatite nanocomposites are very effective in bone tissue engineering and developing medical-grade prostheses owing to their high biological compatibility and efficiency.